COMIC DIGITAL AS INTERACTIVE LEARNING MEDIA IN SEJARAH KEBUDAYAAN ISLAM LESSONS AT MIN 1 PANDEGLANG - Desyi Rosita (el-Moona: Jurnal Ilmu Pendidikan Islam, 2021)
Interactive learning, actually is not on the results but rather on the learning process, namely a teacher can make it easier for students to understand and master the lesson, students are not charged with memorizing activities but how to understand that makes it easier to understand quickly, especially Islamic Cultural History (SKI) lessons, because That's the need for tools or media as a support. Media has an important role in achieving learning objectives. The purpose of this study was to determine interactive learning through digital comic strips (comic strips) for sixth grade students as a learning solution. The method used in this research is descriptive qualitative. The data from this study were obtained through observation and interviews taken from several respondents as informants. The results of the study indicate that interactive learning through digital comic media is a learning solution that meets the criteria and provides a new nuance in learning. Thus, educators must be able to master the strategies used and maximize learning by using up to date media.